Generation of alloreactive cytolytic T lymphocytes by immobilized anti-CD3 monoclonal antibodies. Analysis of requirements for human cytolytic T-lymphocyte differentiation. - De Jong, R (1990)
Requirements for the induction of human cytolytic T-lymphocyte (CTL) activity were studied in a monocyte-free T-cell activation system that uses immobilized anti-CD3 monoclonal antibodies (mAb) as a stimulus. Alloreactive CTL with specificity for HLA-A and -B locus antigens could be demonstrated within 2 days after the initiation of activation. CTL induction in purified T cells initiated by an optimal concentration of immobilized anti-CD3 mAb was not enhanced by the addition of monocytes or exogeneous cytokines, whereas addition of anti-CD25 mAb largely blocked the response. Upon suboptimal anti-CD3 mAb stimulation, addition of recombinant interleukin (rIL)-2, rIL-1 and rIL-4, but not recombinant interferon-gamma (IFN-gamma) or rIL-6, potentiated the development of CTL activity. Finally it was shown that immobilized anti-CD3 mAb induced significant levels of CTL activity in both purified CD4+ and CD8+ cells. This study indicates that the requirement for cytokines in the differentiation of CTL precursors depends on the strength of the activation signal delivered through the T-cell receptor.